Long-Term Effect of Endoscopic Evacuation for Large Basal Ganglia Hemorrhage With GCS Scores ≦ 8 - Liu, Haixiao; Wu, Xun; Tan, Zhijun; Guo, Hao; Bai, Hao; Wang, Bodong; Cui, Wenxing; Zheng, Longlong; Sun, Feifei; Zhang, Xiaoyang; Fan, Ruixi; Wang, Ping; et al. (Frontiers in Neurology, 2020)
Aims: The surgical evacuation, including stereotactic aspiration, endoscopic evacuation, and craniotomy, is the most effective way to reduce the volume of intracerebral hemorrhage. However, credible evidence for the effects of these techniques is still insufficient. The present study explored the long-term outcomes of these techniques in the treatment of basal ganglia hematoma with low Glasgow Coma Scale (GCS) scores (≤8) and large-volume (≥40 ml), which were predictors of high mortality. Methods: Two hundred and fifty-eight consecutive patients were reviewed retrospectively. The primary and secondary outcomes were 6-months mortality and 6-months modified Rankin Scale score, which were assessed by a multivariate logistic regression model. Results: Compared with the endoscopic evacuation group, the mortality was significantly higher in the stereotactic aspiration group (OR 6.858, 95% CI 3.146–14.953) and open craniotomy group (OR 3.315, 95% CI 1.497–7.341). Age (OR = 2.237, 95% CI 1.290–3.877) and herniation (OR = 2.257, 95% CI 1.172–4.348) were independent predictors for mortality. No significant difference in the neurological functional outcome was found in the stereotactic aspiration group (OR 0.501, 95% CI 0.192–1.308) and the craniotomy group (OR 0.774, 95% CI 0.257–2.335) compared with the endoscopic evacuation group. Conclusion: Endoscopic evacuation significantly decreased the 6-months mortality in patients with hemorrhage ≥40 ml and GCS ≤ 8.